2015
DOI: 10.1210/jc.2015-1346
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes Following Therapy in Differentiated Thyroid Carcinoma: NTCTCS Registry Analysis 1987–2012

Abstract: We confirm previous findings that T/NTT followed by RAI is associated with benefit in high-risk patients, but not in low-risk patients. In contrast with earlier reports, moderate THST is associated with better outcomes across all stages, and aggressive THST may not be warranted even in patients diagnosed with distant metastatic disease during follow-up. Moderate THST continued at least 3 years after diagnosis may be indicated in high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(104 citation statements)
references
References 41 publications
3
101
0
Order By: Relevance
“…This approach signiicantly decreases mortality and recurrence in DTC [63]. The exact amount of needed suppression is not clear but studies show that reducing TSH level to less than 0.1mU/L improves clinical outcome; however moderate reductions are beneicial [64, 65]. This treatment may have some complications like osteoporosis in postmenopausal women or angina and atrial ibrillation in elderly patients; so the risk of complications should be weighed against the risk of proliferation of malignant cells [66].…”
Section: Diagnosis and Management Of Head And Neck Cancer 64mentioning
confidence: 99%
“…This approach signiicantly decreases mortality and recurrence in DTC [63]. The exact amount of needed suppression is not clear but studies show that reducing TSH level to less than 0.1mU/L improves clinical outcome; however moderate reductions are beneicial [64, 65]. This treatment may have some complications like osteoporosis in postmenopausal women or angina and atrial ibrillation in elderly patients; so the risk of complications should be weighed against the risk of proliferation of malignant cells [66].…”
Section: Diagnosis and Management Of Head And Neck Cancer 64mentioning
confidence: 99%
“…However, globally, there is no consensus about when patients with RAI refractory DTC should start MKIs when they are asymptomatic and progressing, and such information, supported by broader evidence-based and long-term outcome data, is needed to guide treatment decisions (Carhill et al 2015). …”
Section: Introductionmentioning
confidence: 99%
“…This prospective study showed that maintaining serum TSH values in the normal–subnormal range improved the overall survival of patients with stage I–IV disease (see figures 1a–1d), increased the overall survival of patients with distant metastases (figure 1e), and also increased the disease free survival of patients with stage I–III disease (8). Aggressive TSH suppression to achieve a subnormal-undetectable TSH was not necessary to achieve these benefits.…”
Section: The Basics Of Treating Hypothyroidismmentioning
confidence: 85%
“…In contrast with earlier reports from the NTCTCSG (9, 10), aggressive TSH suppression may not be warranted, even in patients diagnosed with distant metastatic disease during follow-up. These latter patients had decreased survival if their TSH values were maintained in the normal-elevated range, compared with the survival of those with undetectable-subnormal and subnormal-normal TSH values (8) However, there was no additional benefit of undetectable-subnormal TSH values compared with subnormal-normal values.…”
Section: The Basics Of Treating Hypothyroidismmentioning
confidence: 99%